Alternating hyperthyroidism and hypothyroidism in Graves' disease. Issue 9 (9th July 2018) - Wong, Mimi; Inder, Warrick J.
Key Clinical Message: Spontaneously oscillating thyroid function in Graves' disease is a rare phenomenon. Switching between TSH receptor stimulating antibodies (TSAb) and TSH receptor blocking antibodies (TBAb) most likely accounts for presentations of alternating hyperthyroidism and hypothyroidism. To achieve stability of thyroid function, definitive therapy is recommended to remove the pathological thyroid. Abstract : Spontaneously oscillating thyroid function in Graves' disease is a rare phenomenon. Switching between TSH receptor stimulating antibodies (TSAb) and TSH receptor blocking antibodies (TBAb) most likely accounts for presentations of alternating hyperthyroidism and hypothyroidism. To achieve stability of thyroid function, definitive therapy is recommended to remove the pathological thyroid.